Future of the Prophetic : Israel's Ancient Wisdom Re-presented. - Ellis, Marc H. (Fortress Press, 2014)
Future of the Prophetic argues that in the persistence of the prophetic, the legacy of the ancient Jewish world spread beyond the boundaries of the Jewish community and took root throughout the world. This dual rooting unveils a startling but promising new context: a re-presentation of the prophetic from outside the Jewish world to the Jewish community. The new situation of contemporary prophetic challenges the fixed religious landscape by reversing traditional boundaries, eschewing power and privilege, and brokering peace through solidarity and common struggle in ecumenical and interfaith con.